Assessment of sub-clinical mastitis and its associated risk factors in dairy livestock of Lamjung, Nepal - Khanal, T; Pandit, A (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Mastitis is one among the top three threats faced by dairy farmers. The study was carried out to assess sub-clinical mastitis, management practices and associated risk factors for mastitis. MATERIALS AND METHODS: A cross sectional study was conducted in Chandreshwor and Archalbot VDCs of Lamjung district taking 63 dairy livestock randomly each from a herd along with questionnaire survey to respective owner. Tem ml of milk sample from each quarter was taken in a sterilized syringe for further laboratory investigation. California Mastitis Test (CMT) was performed at farmer’s shed. Organisms were identified based on colony characteristics, Gram's staining and various biochemical tests. RESULTS: On CMT, subclinical mastitis was 46.1% (n=29) and 30.15% (n=76) on animal and quarter basis respectively, however, culture showed, 28.6% and 24.2%. Streptococcal mastitis was the commonest (11.1%) followed by coliform (9.5%) and staphylococcal (7.9%). Mastitis was highest in left fore quarter (34.92%) followed by left hind (31.76%), right hind (28.57%) and right fore (25.39%). Coliform & Staphylococcal mastitis was highest in left fore and right hind quarter respectively. Most of dairy animals (86%) were on zero grazing, 30% (n=19) of the farmers had forage trees and only 29% (n=18) had known about subclinical mastitis. The average milk production was 3.5 ±1.47 liters. Subclinical mastitis was associated significantly (p<0.01) with livestock yielding more than 3 lt per lactation. CONCLUSIONS: There was high prevalence of subclinical mastitis in dairy livestock at Lamjung due to poor management, unhygienic shed, and little knowledge on subclinical mastitis. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8322 Int J Infect Microbiol 2013;2(2):49-54